2019
DOI: 10.3389/fncel.2019.00356
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Induction Re-establishes a Proper Neuronal Differentiation Program in Friedreich’s Ataxia Neural Stem Cells

Abstract: Frataxin deficiency is the pathogenic cause of Friedreich’s Ataxia, an autosomal recessive disease characterized by the increase of oxidative stress and production of free radicals in the cell. Although the onset of the pathology occurs in the second decade of life, cognitive differences and defects in brain structure and functional activation are observed in patients, suggesting developmental defects to take place during fetal neurogenesis. Here, we describe impairments in proliferation, stemness potential an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 78 publications
(139 reference statements)
2
43
1
Order By: Relevance
“…Along this line, we found a decrease of NRF2 and GPX4, altered expression of genes controlling iron metabolism and increased susceptibility to ferroptosis in brown adipocyte precursors, as well as in mature adipocytes isolated from KIKO mice. These results are in accordance with the findings pointing to oxidative stress, iron overload, and ferroptosis among the main pathogenic factors in FRDA 6,27,[53][54][55] . Interestingly, NRF2, besides being an up-stream modulator of the expression of antioxidant genes and protection against oxidative stress/ferroptosis 56,57 , positively regulates enzymes involved in mitochondrial oxidation of FAs 29 and adipogenesis 58,59 .…”
Section: Discussionsupporting
confidence: 92%
“…Along this line, we found a decrease of NRF2 and GPX4, altered expression of genes controlling iron metabolism and increased susceptibility to ferroptosis in brown adipocyte precursors, as well as in mature adipocytes isolated from KIKO mice. These results are in accordance with the findings pointing to oxidative stress, iron overload, and ferroptosis among the main pathogenic factors in FRDA 6,27,[53][54][55] . Interestingly, NRF2, besides being an up-stream modulator of the expression of antioxidant genes and protection against oxidative stress/ferroptosis 56,57 , positively regulates enzymes involved in mitochondrial oxidation of FAs 29 and adipogenesis 58,59 .…”
Section: Discussionsupporting
confidence: 92%
“…A conditional frataxin knockout mouse line showed decreased NRF2 expression and increased KEAP1 expression (Anzovino et al, 2017) and in the mouse motor neuron cell line NSC-34, frataxin shRNA likewise reduced NRF2 expression and activity (Paupe et al, 2009). In contrast, inducing NRF2 with sulforaphane or the NRF2activating compound EPI-7443 in neural stem cells isolated from a Friedrich's ataxia mouse model was shown to reestablish proper differentiation which was previously impaired in those cells (La Rosa et al, 2019). In cultured motor neurons, sulforaphane also increased frataxin levels as well as neurite number and extension (Petrillo et al, 2017).…”
Section: Nrf2 and Friedrich's Ataxiamentioning
confidence: 99%
“…The mechanism proposed in those studies highlighted an abnormal distribution of actin fibers causing a defective binding of the NRF2-KEAP1 complex and the failure of NRF2 nuclear translocation [58]. Beside this, defects in redox homeostasis and in the NRF2-dependent antioxidant response are reported in many other models of the disease, such as in the hearts of the muscle creatine kinase (MCK) conditional frataxin knockout mice [56], in dorsal root ganglia (DRG) neurons dissected from the YG8R mice [59] and in neural stem cells (NSCs) isolated from the knock-in knock-out (KIKO) FA mouse model [10]. These numerous reports strongly address therapeutic approaches aimed at re-establishing a functional NRF2 signaling in FA.…”
Section: Nrf2 Signaling Network Overview and Impairments In Famentioning
confidence: 99%
“…In line with this principle, as has been observed in other neurodegenerative diseases where oxidative stress is increased [76], in FA the frataxin deficiency-induced oxidative stress should stabilize NRF2 and induce an up-regulation of ARE-dependent gene transcription. Nevertheless, NRF2 signaling is impaired in several FA cells and animal models [10,36,[56][57][58][59]77]. The mechanisms underlying NRF2 deficiency in FA are still poorly understood, although, starting from the first decade of the 2000s some studies reported a reduced antioxidant defense as a consequence of frataxin depletion [78], while the over-expression of frataxinwas able to potentiate the antioxidant responses [79].…”
Section: Nrf2 Signaling Network Overview and Impairments In Famentioning
confidence: 99%
See 1 more Smart Citation